SAT0486 Macrophage Activation Syndrome and Familial Hemophagocytic Lymphohistiocytosis: Is Their Clinical Phenotype Really Similar?. (9th June 2015) - Horne, A.; Minoia, F.; Davì, S.; Bovis, F.; Rosina, S.; Lehmberg, K.; Weitzman, S.; Insalaco, A.; Wouters, C.; Shenoi, S.; Espada, G.; Ozen, S.; et al.
Abstract : Background: Macrophage activation syndrome (MAS) is a potentially life-threatening complication of systemic juvenile idiopathic arthritis (sJIA). It is common view that sJIA-associated MAS bears a close clinical resemblance to the group of hemophagocytic lymphohistiocytosis (HLH) syndromes, including familial HLH (FHL). This has led to suggest the use of the HLH-2004 guidelines to diagnose MAS in sJIA. However, MAS develops in the context an underlying highly inflammatory condition, whereas FHL is a primary disorder with genetic basis. It is, thus, conceivable that some differences exist in the clinical expression and severity of the two conditions. However, their clinical picture has previously been compared only in a small study 1 Objectives: To compare the demographic, clinical, laboratory and histopathologic features of sJIA-associated MAS and FHL Methods: Data on sJIA-associated MAS were collected by pediatric rheumatologists and pediatric hemato-oncologists in a large multinational collaborative effort 2 . Data on FHL patients were gathered from the HLH-94 and HLH-2004 trials 2 . Clinical and laboratory features at disease onset were compared between by means of Mann-Whitney U test or chi-square/Fisher exact test, as appropriate Results: A total of 620 patients were enrolled: 362 (58.4%) with sJIA-associated MAS and 258 (41.6%) with FHL. The main differences in demographic, clinical, laboratory and histopathologic features between the two patient groups are presented in Table 1 Conclusions: Although MAS and FHL showed similar clinical features and laboratory abnormalities, the frequency of most clinical manifestations and the severity and trend of laboratory changes were different. FHL patients had greater frequency of hepatosplenomegaly and more profound cytopenia, hypofibrinogenemia and hypertransaminasemia, whereas MAS patients had higher levels of ferritin and LDH. The prevalence of CNS disease was comparable between the two groups. Hemophagocytosis was detected more commonly in FHL. The observed differences suggest the use of different diagnostic criteria for the two conditions References: Lehmberg et al. Differentiating macrophage activation syndrome in systemic juvenile idiopathic arthritis from other forms of hemophagocytic lymphohistiocytosis. J Pediatr 2013;162:1245-51. Minoia et al. Clinical features, treatment and outcome of macrophage activation syndrome complicating systemic juvenile idiopathic arthritis. A multinational, multicentre study of 362 patients. Arthritis Rheumatol 2014;66:3160-9. Henter et al. HLH-2004: diagnostic and therapeutic guidelines for hemophagocytic lymphohistiocytosis. Pediatr Blood Cancer 2007;48:124-31 Disclosure of Interest: None declared